A link between hypercholesterolemia and chronic lymphocytic leukemia. Issue 4 (2nd April 2016) - Chow, Signy; Buckstein, Rena; Spaner, David E.
Abstract: The incidence of hypercholesterolemia and its possible relationship with clinical course were determined by reviewing the records of 231 consecutive patients presenting to a specialized Chronic Lymphocytic Leukemia (CLL) clinic. Evidence for elevated cholesterol was found in up to 174/231 patients (75%) based on existing use of statins (107 patients) or non-fasting low-density lipoprotein cholesterol levels greater than 2.5 mM. Excluding patients with 17p deletions, time to first treatment (TFT) was prolonged if patients were taking cholesterol-lowering statins (57.5 (IQR = 32, 77) vs 36 (IQR = 11, 100) months, p  < 0.02). If patients were prescribed statins after being diagnosed with CLL, TFT was longer than if they were taking statins before the diagnosis. These observations suggest there is a high incidence of hypercholesterolemia in CLL patients and cholesterol-lowering may impact the disease course.